How to draw cute animals - Nguyen, Angela (Sterling Children's Books, 2018)
Step-by-step instructions teach kids how to draw a menagerie of adorable creatures, from cats, dogs, hedgehogs, and hamsters to dolphins, bunnies, swans, and unicorns. Includes miscellaneous animal facts and a brief introduction that explains the popular Kawaii style of art.